Innovation Strategies and Facilities Determine Competitive Advantages in Cafe - Kenjiorlando; Hommy Dorthy Ellyany Sinaga (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
This study aims to find out how much influence innovation strategies and facilities have in determining the competitive advantage of Titik Koma's Coffee Cafe. Population in this study is consumers from Titik Koma's Coffee Cafe. The technique for determining the number of samples used in this study is the Hair formula. The analysis data used the multiple linear regression analysis method. The results of the analysis provide the equation Competitive Advantage = 1.374 + 0.050 Innovation Strategy + 0.532 Facilities + e. The results of the t test showed that the innovation strategy variable had a positive and insignificant effect on the competitive advantage at the Titik Koma's Coffee Cafe where tcount (1,132) > ttable (1.9847), the facility variable had a positive and significant effect on the competitive advantage at the Titik Koma's Coffee Cafe where tcount (9,320) > ttable (1.9847). The results of the F test showed that Fcount (176.078) > Ftable (3.09) which means that the independent variables simultaneously affected the bound variable. The results of the determination coefficient (R2) test show that 78.4% of the consumer satisfaction variables are influenced by innovation strategies and facilities while the remaining 21.6% are influenced by other variables.